Model Authentic Assessment dalam Pembelajaran Sastra Terintegrasi Karakter Multikultural - Sri Wahyuni; Ari Ambarwati; NFN Junaidi; Junaidi Ghony; Zulkifli Osman (Jentera: Jurnal Kajian Sastra, 2022)
Character education, incredibly multicultural characters, must be instilled in students significantly to minimize conflict in a society, including the plural and heterogeneous Indonesian society. Planting multicultural characters, especially in academic learning, can be done by integrating these characters in the learning and assessment process. The research goals to develop an assessment activity and an authentic assessment instrument model in academic learning that integrates multicultural characters. The research method is Research and Development (R&D). The research uses ADDIE model developed by Reiser and Molley, namely Analysis, Design, and Development. The results of the research formulates two findings, first, the model of assessment activities in literary learning that integrates multicultural characters can be done through (1) social studies of life in literary works, (2) through appreciation of literary works that contain multicultural values,(3) through role-playing in drama, (4) through a comparison of literary works, and (5) through field experience when appreciating and writing literary works. Second, the authentic assessment instrument model in academic learning that integrates multicultural characters are developed through the techniques of (1) observing multicultural attitudes, (2) self-assessment related to multicultural attitudes, (3) peer assessment related to multicultural attitudes, (4) direct questions about multicultural attitudes furthermore (5) personal reports related to multicultural attitudes.